2019
DOI: 10.6061/clinics/2019/e981
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum Activin A in chronic obstructive pulmonary disease with skeletal muscle wasting

Abstract: OBJECTIVE: Muscle wasting contributes to the reduced quality of life and increased mortality in chronic obstructive pulmonary disease (COPD). Muscle atrophy in mice with cachexia was caused by Activin A binding to ActRIIB. The role of circulating Activin A leading to muscle atrophy in COPD remains elusive. METHODS: In the present study, we evaluated the relationship between serum levels of Activin A and skeletal muscle wasting in COPD patients. The expression levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Activin A can stimulate broblast differentiation into myo broblasts inducing the proliferation of lung broblasts, airway smooth muscle cells, and bronchial epithelial cells [18] . Levels were raised in airways severe asthma [19] and in the serum of patients with COPD compared to healthy controls [20] . Activin A and activin B are expressed at increased levels in alveolar epithelial cells and in ammatory cells in patients with idiopathic pulmonary brosis [6] , and the activin A antagonist follicle suppressor can also reduce bleomycin-induced pulmonary brosis [17] .…”
Section: Discussionmentioning
confidence: 96%
“…Activin A can stimulate broblast differentiation into myo broblasts inducing the proliferation of lung broblasts, airway smooth muscle cells, and bronchial epithelial cells [18] . Levels were raised in airways severe asthma [19] and in the serum of patients with COPD compared to healthy controls [20] . Activin A and activin B are expressed at increased levels in alveolar epithelial cells and in ammatory cells in patients with idiopathic pulmonary brosis [6] , and the activin A antagonist follicle suppressor can also reduce bleomycin-induced pulmonary brosis [17] .…”
Section: Discussionmentioning
confidence: 96%
“…Functionally, activin A as a remarkable biological actor in asthma, chronic obstructive lung disease (COPD) and lung cancer were supported in recent studies [11,12]. In our previous study, we found that levels of serum Activin A were increased in COPD patients with skeletal muscle wasting [13]. Furthermore, we recently identi ed that higher expression of serum Activin A was associated with poor prognosis of Community-Acquired Pneumonia (CAP) (not yet published).…”
Section: Introductionmentioning
confidence: 81%
“…The clinical investigation found that a higher concentration of Activin A in bronchoalveolar uid (BALF) could predict poorer mortality in ARDS patients [28]. Our previous study found that compared with healthy individuals, patients with chronic obstructive pulmonary disease have elevated levels of serum Activin A correlated with TNF-α expression [13]. Furthermore, we recently revealed that increased levels of Activin A in serum not in uenced by etiology play a more a more effective predictor of hospital mortality in CAP patients (not yet published).…”
Section: Discussionmentioning
confidence: 99%
“…Increased circulating pro-cachectic factors (e.g., activin A) have been observed in patients with cancer (22,61), in patients with chronic obstructive pulmonary disease (23), and now in patients with CKD. Furthermore, our findings also suggest that blood levels of activin A increased with the progression of renal impairment.…”
Section: Discussionmentioning
confidence: 99%